Enhancing the interaction between cellulose and dilute aqueous ionic liquid solutions and its implication to ionic liquid recycling and reuse. (1st February 2022) - Zhang, Jinxu; Zou, Dongzhe; Zhai, Siyu; Yan, Yin; Yang, Hua; He, Chunyong; Ke, Yubin; Singh, Seema; Cheng, Gang
Abstract: Cellulose-dissolving ionic liquids (ILs) have been used in biomass pretreatment for over a decade. Cellulose solubility in the ILs is strongly inhibited by water, which has negative impacts on IL pretreatment and reuse of the recycled ILs. Here, a distillation and aeration apparatus was used as the reactor for biomass pretreatment in dilute aqueous IL solutions and in recycled IL liquor without drying or purification. Four biomass types, switchgrass, miscanthus, sorghum and pine, were studied. X-ray diffraction (XRD) was used to measure the interaction between biomass and the IL. Small angle neutron scattering (SANS) was applied to monitor the changes of the pore structure in wet biomass samples. Satisfactory enzymatic hydrolysis results were obtained among all the pretreated samples. Graphical abstract: Unlabelled Image